The Power of Classroom Libraries and Pre-service Teachers - Sonja Ezell (The Advocate, 2016)
This paper explores how critical classroom libraries are for student success. Research indicates that students who have access to classroom libraries read more and their reading achievement improves. This study investigates the picture-book genre preferences of pre-service teachers and the implications for the books and genres that scored both high and low on the survey. In addition, this study highlights the plight of students who reside in book desserts and do not have abundant opportunities to obtain books outside of the school community.